Exposure to leisure noise and intermittent tinnitus among young adults in Bavaria: longitudinal data from a prospective cohort study. (1st February 2022) - Weilnhammer, Veronika; Gerstner, Doris; Huß, Jonas; Schreiber, Fabian; Alvarez, Carmelo; Steffens, Thomas; Herr, Caroline; Heinze, Stefanie
Abstract: Objectives: To investigate the association between total leisure noise exposure and intermittent tinnitus among young adults. Design: Data were obtained from the Ohrkan study, an ongoing prospective cohort study conducted in South Germany since 2009. Information about exposure to impulse and leisure noise, tinnitus occurrences, sociodemographic variables, and self-rated hearing ability were analysed at four time points over a period of seven and a half years. Study sample: Participants of the Ohrkan cohort study, who provided data about the occurrence of tinnitus for all surveys ( n = 1028). Results: Intermittent tinnitus was reported in the majority of the sample (60%). The risk for intermittent tinnitus increased with higher sound pressure levels from exposure to leisure noise (full model (Odds Ratio, 95%CI): 80–<85dB(A): 1.41 [1.13–1.78], 85–<90dB(A): 1.73 [1.38–2.16], >90dB(A): 2.04 [1.59–2.61]). Visiting nightclubs was a major contributor to this relationship. Of the considered covariables, self-rated hearing as "poor", and growing up in a single-parent household were significantly associated with intermittent tinnitus. Conclusion: Intermittent tinnitus is very frequent among young adults and is associated with high levels of leisure noise exposure. To prevent intermittent tinnitus, reduced sound pressure levels and the use of hearing protection are necessary.